MONOPOLI DAN UU ANTI TRUST - Salsa Billa Dwi Rianto; Ismi Indah Pertiwi; Habibi Jubran; Muhammad Arfan Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the role of the Anti-Trust Law in regulating and adjudicating monopolistic practices and unfair business competition in Indonesia. As an integral part of business law, the Anti-Trust Law has an important role as a regulator and adjudicator in creating a fair and competitive business climate. The research method used is a literature review that includes an analysis of laws and regulations, regulations, and court decisions related to business competition cases. The results of the study indicate that although the existing legal framework is adequate, its implementation still faces various challenges, such as limited resources, low legal awareness of business actors, and bureaucratic obstacles. The discussion highlights the importance of the role of the Business Competition Supervisory Commission (KPPU) as an institution responsible for supervision and law enforcement, as well as the role of the judiciary in adjudicating disputes related to monopolistic practices and unfair business competition.